PENGARUH SELF CONTROL TERHADAP RESIDIVISME NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIA PADANG - Shamirazie, Luthfie Al Fayed; Wibowo, Padmono (Universitas Nusa Cendana, 2024)
This study examines how Self Control affects Prisoner Recidivism at the Class IIA Padang Correctional Institution. The sampling technique used in this study used the formula from Krejcie and Morgan. So that the number of samples obtained was 165 recidivist prisoners out of 286 recidivist prisoners of the Class IIA Padang Correctional Institution. The simple linear regression method was used in analyzing the research data. From the results of data processing carried out, it is known that Self Control affects Prisoner Recidivism at the Class IIA Padang Correctional Institution with an influence level (R-Square) of 64.3%. The findings of this study can help officers to pay more attention to the sustainability of factors that affect Self Control which is an important part of a recidivist's life. In addition, this research contributes in a new way, namely as literature in the field of corrections. Keywords: Self Control; Recidivism; Correctional Institution